PBL session conducted for second year undergraduate students of medicine and dentistry at Universal College of Medical Sciences Nepal: Perception of the participants - Mal, PiryaniRano; Suneel, Piryani; Narayan, Gautam (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: Problem-based-learning (PBL) is generally recognized as a student centered instructional approach. Universal College of Medical Sciences Nepal introduced PBL to second year MBBS and BDS students in July 2019.This study assessed the perceptions of students of second year MBBS and BDS who participated in PBL session. Material and Methods: This was a cross-sectional questionnaire-based study assessing perceptions of the participant students. The validated questionnaire was used for the collection of data at the end of PBL session. The questionnaire comprised of two parts; Part I- Students’ perceptions and attitude towards PBL (9 statements) and Part II Students’ perceptions about the role of tutor in PBL(11 statements).Data were analyzed using SPSS version 21. The frequency, mean and standard deviation were computed and t test was used for the comparison of responses on statements of MBBS and BDS groups. Results: The mean scores on7 out of 9 statements on students’ perceptions and attitude towards PBL was higher than fourat Likert scale 1-5 (5=strongly agree, 4=agree, 3=to some extent agree, 2=disagree, 1=strongly disagree) and on 2 statements was higher than 3.5. The mean scores on all the statements with regard to students’ perception about the role of tutor in PBL were higher than four. The mean scores of both MBBS and BDS groups of students on all statements were compared; the significant differences were obtained only on 2 statements out of 20. Conclusion: The perceptions and attitude of students towards PBL and perceptions about the role of tutor were positive.